Cyber-troops, digital attacks, and media freedom in Indonesia. Issue 3 (4th May 2022) - Masduki,
ABSTRACT: This article examines media freedom in Indonesia in the age of social media and cyber-troops. Scholars and media advocates have extensively debated social media's effects on freedom of expression and media, with some arguing that it offers room for citizens' voices to be heard. Countering this argument, this article explores how social media-based attackers have undermined media freedom in Indonesia. It does so through in-depth analysis of digital attacks conducted before and after the 2014 and 2019 presidential elections, during which politician-sponsored actors spread disinformation and waged cyberwar to achieve political goals. This study employs a descriptive qualitative method to contribute to the broader debate on media freedom and digital authoritarianism in the context of Indonesia's digital communication landscape. This paper shows how digital attacks and attackers are increasingly violating the media's autonomy and stymieing its service of the public interest. This paper expands on previous observations of media freedom, which have traditionally held that state intervention and media ownership concentration are political authorities' main means of disciplining critical media and journalists.